Post-Construction Challenges in Infrastructure Development: An Ecotheological Perspective on Achieving SDGs - Andriani Andriani (Fenomena, 2024)
The construction of Dhoho Airport in Kediri is expected to stimulate local economic growth but also presents notable risks to achieving the 17 Sustainable Development Goals (SDGs). This study provides a critical evaluation from an Eco-Theology perspective, an approach rarely used in Indonesian infrastructure and SDG research, thereby offering fresh ethical-environmental insights. Using a qualitative descriptive method, data were gathered from literature, official documents, and interviews. The findings reveal partial SDG achievement (Goals 1, 4, 8, 11, and 17), while others remain unmet (Goals 2, 3, 5–7, 12–16). Major challenges include conversion of productive agricultural land, heightened noise and air pollution (noise levels reaching 43.72% in Grogol Village), and increased risks of landslides and flooding due to inadequate water management in hilly areas. Originality and Significance this research fills a gap by integrating eco-theological ethics into infrastructure evaluation, highlighting moral responsibilities often overlooked in policy debates on sustainability. The study bridges theology, ecology, and development studies, emphasizing that sustainable infrastructure must address not only technical and economic goals but also humanity’s ethical duty to protect and care for the environment. Pembangunan Bandara Dhoho di Kediri diharapkan dapat mendorong pertumbuhan ekonomi lokal, namun juga menimbulkan risiko signifikan terhadap pencapaian 17 Tujuan Pembangunan Berkelanjutan (SDGs). Studi ini memberikan evaluasi kritis dari perspektif Eco-Theology, pendekatan yang jarang digunakan dalam penelitian infrastruktur dan SDGs di Indonesia, sehingga menawarkan wawasan etis-lingkungan yang baru. Menggunakan metode deskriptif kualitatif, data dikumpulkan dari literatur, dokumen resmi, dan wawancara. Hasil penelitian menunjukkan pencapaian sebagian SDGs (Tujuan 1, 4, 8, 11, dan 17), sementara yang lain belum terpenuhi (Tujuan 2, 3, 5–7, 12–16). Tantangan utama meliputi konversi lahan pertanian produktif, peningkatan polusi suara dan udara (tingkat kebisingan mencapai 43,72% di Desa Grogol), serta risiko longsor dan banjir yang meningkat akibat pengelolaan air yang tidak memadai di daerah berbukit. Keaslian dan Signifikansi penelitian ini mengisi celah dengan mengintegrasikan etika ekoteologi ke dalam evaluasi infrastruktur, menyoroti tanggung jawab moral yang sering diabaikan dalam debat kebijakan tentang keberlanjutan. Studi ini menjembatani teologi, ekologi, dan studi pembangunan, menekankan bahwa infrastruktur berkelanjutan harus tidak hanya memenuhi tujuan teknis dan ekonomi tetapi juga kewajiban etis manusia untuk melindungi dan merawat lingkungan.